2009
DOI: 10.1007/s12298-009-0012-z
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry of fruit softening: an overview

Abstract: Softening is a developmentally programmed ripening process, associated with biochemical changes in cell wall fractions involving hydrolytic processes resulting in breakdown of cell-wall polymers such as cellulose, hemicelluloses and pectin etc. Various hydrolytic reactions are brought about by polygalacturonase, pectin methyl esterase, pectate lyase, rhamnogalacturonase, cellulase and β-galactosidase etc. Besides these enzymes, expansin protein also plays an important role in softening. Textural changes during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(157 citation statements)
references
References 107 publications
6
143
0
8
Order By: Relevance
“…All the results above showed that PL activity was maintained at a higher level during fruit ripening and softening both in the softer and firmer cultivars. These results were different from respiration climacteric fruit in which PL activity of banana increased gradually in the climacteric period, reaching a peak at the maximum rate of respiration and then gradually declined with reducing of respiration (Payasi et al 2009). …”
Section: Symbolmentioning
confidence: 58%
“…All the results above showed that PL activity was maintained at a higher level during fruit ripening and softening both in the softer and firmer cultivars. These results were different from respiration climacteric fruit in which PL activity of banana increased gradually in the climacteric period, reaching a peak at the maximum rate of respiration and then gradually declined with reducing of respiration (Payasi et al 2009). …”
Section: Symbolmentioning
confidence: 58%
“…The relationship between the two parameters (ICO 2 × mealiness) is also exhibited in the high Pearson correlation (Table 2). Perhaps the higher ICO 2 in fruit with high mealiness is related to the intercellular space reduction by the soluble pectin, whereby fruit softening is a result of hydrolysis of various cell wall components, such as pectin (Prasanna et al, 2007;Payasi et al, 2009).…”
Section: Quality Analysis After 8 Months Of Storagementioning
confidence: 99%
“…Fruit from the control treatment group showed the highest incidence of mealiness ( Figure 2E), which is related to higher ethylene production and IEC, since they have a high Pearson correlation ( Table 2). The effect of the ethylene on mealiness is related to cell wall enzyme activation (Prasanna et al, 2007;Goulao and Oliveira, 2008;Payasi et al, 2009). On the other hand, the combined application of AVG + NAA, AVG + 1-MCP and AVG + ABS suppressed (p < 0.05) the incidence of mealiness in relation to AVG application in isolation ( Figure 2E).…”
Section: Quality Analysis After 8 Months Of Storagementioning
confidence: 99%
“…For Soh et al (2006), the activity of an isoform of α-galactosidase increases as the papaya fruit loses its firmness. Payasi et al (2009) indicated that the activity of glycosidases such as β-hexosaminidase, α-mannosidase, and α-galactosidase increases in tomato when it is harvested at the fully mature stage. Moreover, Yashoda et al (2007) attributed the softening of ripened mango to the activities of endomannosidase and α-mannosidase.…”
Section: Introductionmentioning
confidence: 99%